Evaluate the use of elliptical finned tubes in heat exchanger design and performance : 'the structural characteristics of finned tubes' - Sizani, Xolile L. (Stellenbosch : Stellenbosch University, 2012)
Thesis (MEng)--University of Stellenbosch, 2000.